ANALYSIS FACTORS OF INFLUENCE THE JOB PERFORMANCE IN SECRETARIAT DAERAH KABUPATEN BANGKALAN MADURA - Surachmad (Fakultas Ekonomi Universitas 45 Surabaya, 2017)
This study aims to examine and analyze the influence of the independent variable is the ability, motivation, opportunity, and discipline of the dependent variable is employee job performance. Sample as many as 50 people. Hypothesis testing is done by using statistical tools Regresion Linier on the degree of accuracy of alpha = 0.05 or 5%. The first hypothesis is proven by the results of 8.464 F count larger than F table with a significance level of 2.810 to 0.000. Statistical analysis showed a significant difference between the capability on the performance of employees, this is based on the calculation and analysis of the results by using statistical test t results t value of 5.313 which indicates that the value of t is greater than t table of 1.701 with a significant degree of 0.000, means that the hypothesis can be accepted. A significant difference between the motivational factor on the performance of employees, this is based on the calculation and analysis of results of research shall use statistical test t results t value of 2.780 which indicates that the value of t is greater than t table of 1.701 with a degree significantly 0,007, means that the hypothesis can be accepted. A significant difference between the factors of chance on the performance of employees, this is based on the calculation and analysis of the results by using statistical test t results t value of 2.116 which indicates that t is greater than t table of 1.701 with a degree significantly by 0,038 , means that the hypothesis can be accepted. And a significant difference between the factors of discipline on the performance of employees, this is based on the calculation and analysis of the results by using statistical test t results t value of 3.922 which indicates that the value of t is greater than t table of 1.701 with a degree significantly 0,000, means that the hypothesis can be accepted. The independent variables that have the greatest Beta value of 0.666 means the motivation is the motivation most dominant influence on the performance of employees, the proposed third hypothesis received or be evidenced